Short-time kinetics of photorefractive gratings recorded under active phase control: an experimental method to materials characterization - Freschi, A. A.; De Vicente, F. S. [UNESP] (Springer Nature, 2020)
The initial speed of photorefractive recording and erasure is investigated in two-wave mixing experiments under carefully controlled grating phase shifts. Results are reported for the full 2π range of possible phase shifts between the refractive-index grating and the projected interference pattern. The technique is especially suited for experiments using continuous light illumination at low light fringe modulations, providing easy measurement of the grating diffraction efficiency in absolute values. Measurements of the short-time kinetics of the space charge field are carried out for a Bi12TiO20 crystal subjected to different charge transport mechanisms (diffusion and drift by an external electric field). A simple rate equation obtained by the Kukhtarev’s theory is used to fit the experimental data, from which important photorefractive parameters such as the dielectric relaxation time and the effective mobility-lifetime product of the photoexcited charge carriers are determined. Additionally, the reduction factor of the electric field due to screening charges can be known in cases where an external field is applied.